KEHILANGAN KEWARGANEGARAAN BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2006 TENTANG KEWARGANEGARAAN REPUBLIK INDONESIA (Tinjauan Yuridis Terhadap Peristiwa Kewarganegaraan Arcandra Tahar dan Gloria Natapradja Hamel) - Adhitia Pradana (MIH Unsoed, 2018)
ABSTRACTWidespread human interaction in the world provides opportunities for marriage between different nations of citizenship. Intermarriage is not uncommon among nations raises a problem, in terms of one's country of origin where the country in which she gave birth or born adopts the same nationality, it will not cause problems. However, when the two countries concerned have different systems, they can lead to circumstances that cause a person holds the status double nationality (bipatride) or instead became stateless altogether (apatride).The issue of citizenship and non-citizenship, whether it concerns the procedure of obtaining and losing citizenship that is behind the author to do this research. This study aimed to analyze the concept of citizenship that apply in the constitutional system of the Republic of Indonesia and also to analyze the loss of citizenship based on Law No. 12 of 2006 on Citizenship of the Republic of Indonesia. To achieve this goal, this research is done by using normative legal research method with prescriptive model. The collected legal material will be studied comprehensively and analyzed deductively by systematic presentation.The results of research and discussion concluded that: First, the concept of citizenship in the constitutional system prevailing in Indonesia based on Law No. 12 of 2006 on Citizenship of the Republic of Indonesia has to clarify and reinforce the position and legal certainty for every citizen of Indonesia, which is in conformity with mandated in the provisions of Article 26 paragraph (1) and Article 6 paragraph (1) of the Constitution of the Republic of Indonesia Year 1945. Second, the loss of citizenship of the Republic of Indonesia based on Law No. 12 of 2006 on citizenship of the Republic of Indonesia may occur due to loss of citizenship by itself, Loss of citizenship with a request, and loss of citizenship due to a marriage. In addition, based on the analysis of jurisdiction over the events lose citizenship Arcandra Tahar and Gloria Natapradja Hamel, it can be concluded that in accordance with the legislation on citizenship of the Republic of Indonesia, materially Arcandra Tahar has no citizenship and against Gloria Natapradja Hamel is a juridicial as a foreign citizen.Keywords : Republic of Indonesia, Citizenship, Losing Citizenship